Wear and life prediction of the U-shaped connecter of transmission line system under strong wind load. (July 2021) - Yi, You; Xiaochun, Nie; Jianping, Zhao; Zhitao, Yan; Min, Liu
Highlights: The wear experiment was carried out by the self-developed testing machine. The wear response of U-shaped rings under the coupling system was analyzed. The relationship between wear loss, axial force and the swing angle was obtained. The proposed life prediction theory was verified by experiments. Abstract: The strong wind environment may cause the wear of various fittings in transmission line system. The bearing capacity of the worn fittings will be greatly reduced, which will threaten the operation safety of transmission line system. Therefore, it is of great significance to investigate the wear of the fittings under strong wind load. The wear experiment of the U-shaped connecter was carried out. The finite element model of the coupling system considering the ground line, insulator string and U-shaped connecter was established. The effects of the span and wind speed on the dynamic characteristics of the fittings were analyzed. The probability distribution of wind speed in Xinjiang region of China was yielded from the measured average and maximum values of wind speed. The Extreme-Value Type I Distribution and Harmonic Synthesis Method were applied to synthesize the wind speed information. The movement angle and internal force of fittings in transmission line system were investigated under various wind speed levels. Based on the wear experiment and finite element analysis of the wear of the U-shaped connecter, the relationship between the wear loss, the axial force and the swing angle was proposed, which can be used to predict the life of U-shaped connecter. The results show that the predicted wear loss of the U-shaped connecters is in good agreement with the actual wear loss of the U-shaped connecters.